Quality and Yield Improvement of Barrel Tin Plating Process for SMX Semiconductor Packages - Kanan, M.M.D.; Zaimi, M.; Manaf, M.E.A.; Pham, N.M. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Most of semiconductor solderability improvement is done using tin. The tin plating can be done in lead frame or barrel. Barrel tin electroplating process for Surface Mount X (SMX) semiconductor packages has a distinct advantage: the ability to finish a greater volume of work for a specified time period. However, as the SMX packages are applied in critical automotive and medical fields, barrel tin plating also faces yield and quality challenges. This work discusses the common rejects and some solutions to improve the quality and yield of barrel tin plating process for SubMinitature version B (SMB) semiconductor packages. Among the common rejects are missing plating, burn mark, unit coupling, lead discoloration and crack package. The  improvement efforts are the introduction of metal ballast to improve conductivity and reduce missing plating, improvement of solution filtration to avoid discoloration, addition of ‘Zig-zag balls’ to reduce  unit coupling, auto tracking of ampere spike that causes crack package and vision system to further screen out rejects. As a result, SMX barrel plating yield can be increased to more than 99.8% and there are continuous effort to further improve yield and quality.